Synergistic effects of polyphenols and exercise on obesity: targeting metabolism, muscle function, and adipose tissue remodeling - Lei, Xiaowei; Rezaei, Mohammad J. (Frontiers in Nutrition, 2025)
Obesity has emerged as an increasingly significant global health dilemma, imposing a considerable strain on healthcare infrastructures globally and markedly heightening the risk of concomitant metabolic disorders. Although regular physical activity and dietary polyphenols are each independently acknowledged for their substantial anti-obesity and metabolic health advantages, the intricate and multifactorial characteristics of obesity necessitate holistic intervention strategies that may surpass the confines of singular therapeutic methodologies. This review amalgamates contemporary scientific literature to investigate the persuasive rationale and empirical evidence supporting the synergistic effects of polyphenols and exercise in addressing obesity. The analysis indicates that their concurrent application can result in improved outcomes across critical physiological domains, encompassing systemic metabolism, muscular functionality, and adipose tissue remodeling. It is noteworthy that integrated interventions have demonstrated a synergistic effect in mitigating weight gain and visceral adiposity, augmenting the browning of white adipose tissue, and enhancing muscle performance as well as recovery. The amalgamation of these two influential modalities presents a promising prospect for the formulation of more effective and comprehensive strategies aimed at the prevention and treatment of obesity, with the potential to address the challenges related to adherence and bioavailability that are often associated with singular interventions.